Proteomic profile of plasma-derived extracellular vesicles from Colombian pregnant women with Plasmodium-soil transmitted helminths coinfection - Jahnnyer A. Martínez-Moreno; Alberto Ayllon-Hermida; Alberto Ayllon-Hermida; Alberto Ayllon-Hermida; Berta Barnadas-Carceller; Berta Barnadas-Carceller; Carmen Fernández-Becerra; Carmen Fernández-Becerra; Carmen Fernández-Becerra; Hernando A. del Portillo; Hernando A. del Portillo; Hernando A. del Portillo; et al. (Frontiers in Malaria)
IntroductionExtracellular vesicles (EVs) are lipid bilayer membrane-enclosed nanoparticles, secreted by all cell types. Information regarding EVs and their molecular cargo in gestational parasitic infections, particularly those caused by Plasmodium and soil-transmitted helminths (STH), remains largely unexplored. This study aimed to perform isolation and molecular characterization of plasma-derived EVs from Colombian pregnant women and compare quantity, size, concentration and protein cargo of those EVs according to the infectious status, to investigate if parasite-derived proteins could be detected as biological cargo of circulating EVs of pregnant women infected with Plasmodium, STH and co-infections.Materials and methodsA descriptive study with 5 groups was performed: 1) Pregnant women with Plasmodium infection (n=10). 2) Pregnant women with STH infection (n=14). 3) Pregnant women with coinfection Plasmodium and STH (n=14). 4) Pregnant women without infection with Plasmodium nor STH (n=10). 5) Non-pregnant women without infection with Plasmodium nor STH (n=6). Plasma-derived EVs were isolated by size exclusion chromatography (SEC) and fractions containing EVs identified by a bead-based flow cytometric assay for CD9; the size and concentration of EVs were quantified by nanoparticle tracking analysis, and proteins associated with EVs were identified by liquid chromatography-mass spectrometry in a pool of samples per study group.ResultsThere were no statistical differences in expression of the CD9 EVs marker among study groups. The size range of EVs was more variable in the three infected groups (100-700 nm) compared to the size range of the uninfected groups (50-300 nm). A total of 823 quantifiable proteins with measurable abundance values were identified within the five study groups. Of the total quantifiable proteins, 758 were identified as human, six proteins pertained to P. vivax, fifteen to Trichiuris trichiura, and one to hookworms. Data are available via ProteomeXchange with identifier PXD051270.DiscussionThis is the first study that identifies proteins from Plasmodium and STH in EVs isolated from pregnant women. The identification of such proteins from neglected tropical parasites accounting for a major burden of disease worldwide, open the possibilities of studying their physiological role during infections as well as exploring them for antigen discovery, vaccine development and biomarker discovery.